COVID-19 Research in Africa: A Bibliometric Analysis (2019-2021) - Shamsudeen Ademola Sanni; Yusuf Olugbenga Aliyu; Vusi Wonderboy Tsabedze; Ntombikayise N Mathabele (Journal of Health Promotion and Behavior, 2024)
Background: The COVID-19 pandemic has generated an unprecedented volume of research globally, with a significant but varied focus on Africa. Given the unique socio-economic and healthcare challenges faced by the continent, understanding the landscape of COVID-19-related research in Africa is crucial. This study aimed to analyse the body of literature focused on Africa, identifying patterns, trends, and the conceptual, intellectual, and social structures underlying the research. By uncovering these elements, the study provides insights into the strengths and gaps within the existing body of work, offering a foundation for future research and policy formulation. Subjects and Method: A quantitative approach was employed to examine 4,290 documents related to COVID-19 research focused on Africa, sourced from the Web of Science (WoS) database between November 1, 2019 to February 1, 2022. The Bibliometrix R-package was utilized for data processing and visualization, enabling the identification of patterns, trends, and underlying structures within the literature. Results: The analysis revealed significant local and international collaboration in COVID-19 research focused on Africa. Four major themes emerged: (1) Health Systems, Policy, Workers, and Public Health; (2) Mental Health, Depression, and Anxiety; (3) COVID-19’s impact on HIV, Poverty, and Children; and (4) its impact on Education. Institutional collaborations were particularly strong among the top five South African universities, highlighting a robust social structure. The productivity of authors conformed to Lotka’s Law, while periodical distribution followed Bradford's Law of Scattering. Keywords Plus and Abstract Words offered a comprehensive description of the research domain. Conclusion: The findings highlight the collaborative nature and thematic focus of COVID-19 research in Africa, emphasizing the importance of international collaboration. Future research should address identified gaps to deepen and enhance the impact of studies in this area.